Administrative pressure, interpersonal relationships, and teachers’ professional identity - Zhu, Bao; Zhai, Shiting (Frontiers in Psychology, 2025)
Understanding teachers’ professional identity is significant for promoting their professional development, cultivating a high-quality teaching force, and achieving a high-quality education system. This paper empirically analyzes the impact of administrative pressure on teachers’ understanding of professional identity based on data from the China Education Panel Survey using the order probit model to reveal the mechanisms at play in this relationship. Administrative pressure was found to inhibit teachers’ professional identity significantly. The conclusions hold after using conditional mixed regression to deal with endogeneity and robustness tests using various strategies. Heterogeneity analyses revealed that the inhibitory effect of administrative pressure was more pronounced for female teachers and teachers in rural areas. Mechanistic tests indicated two channels for this inhibition—by decreasing teachers’ job satisfaction and increasing teachers’ burnout. The moderating effects tests also showed that the inhibitory effect was relatively weaker when teachers’ interpersonal relationships were better. This study enriches and deepens our understanding of administration and teachers’ professional development, provides new empirical evidence for understanding how administrative pressure affects teachers’ professional identity, and provides a theoretical basis for educational administrations to formulate more effective educational policies and management strategies.